Risk factors of new-onset glucose abnormalities in idiopathic membranous nephropathy patients on glucocorticoid plus tacrolimus - Jin Li; Hui-shu Han; Shu-long Wang; Yan Bao; Yi-qun Peng (Editorial Department of Journal of Clinical Nephrology, 2023)
Objective To explore the risk factors for new-onset glucose abnormalities in patients of idiopathic membranous nephropathy (IMN) on glucocorticoid plus tacrolimus. Methods From August 2019 to January 2022, 118 patients with a diagnosis of IMN via renal biopsy were recruited from First Affiliated Hospital of Xinxiang Medical University. General profiles and laboratory test parameters were collected before tacrolimus dosing plus glucocorticoid. According to whether or not new glucose abnormalities occurred during follow-ups, they were assigned into two groups of normal glucose (n=76) and abnormal glucose (n=42). The risk factors were examined for new-onset glucose abnormalities. Results Age[（51.0±10.1）：（52.0±8.1）], urinary protein{[4577.91（3256.66，7289.84）mg/24h：[6721.26（4079.30，10275.77）mg/24h]}, glycated hemoglobin[（4.93±0.41）%：（5.15±0.33）%], body mass index (BMI)[（25.20±3.66）kg/m2：（26.71±3.47）kg/m2] and homeostatic model assessment of insulin resistance（HOMA-IR）[1.60（1.08，2.17）：2.27（1.83，3.42）]were higher in normal glucose group (P< 0.05). However, no significant differences existed in gender, family history of diabetes, triglycerides, cholesterol, serum albumin, phospholipase A2 receptor antibody or remission rate. Logistic regression analysis revealed that advanced age (OR=1.062), elevated glycated hemoglobin (OR=4.099), BMI (OR=1.144) and HOMA-IR (OR=1.213) were risk factors for new-onset glucose abnormalities. Conclusions IMN patients on tacrolimus regimen with advanced age, elevated basal glycated hemoglobin, BMI or concurrent insulin resistance are more prone to abnormal blood glucose. Individuals with abnormal blood glucose have longer time to achieve a remission of urinary protein than counterparts with normal blood glucose.